The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2325967117726494
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Postoperative Recurrence of Instability After Arthroscopic Bankart Repair in Athletes

Abstract: Background:Several risk factors for the postoperative recurrence of instability after arthroscopic Bankart repair have been reported, but there have been few detailed investigations of the specific risk factors in relation to the type of sport.Purpose:This study investigated the postoperative recurrence of instability after arthroscopic Bankart repair without additional reinforcement procedures in competitive athletes, including athletes with a large glenoid defect. The purpose of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 30 publications
(50 reference statements)
5
64
0
Order By: Relevance
“…This suggests that the type of sport also has a significant effect on recurrence, independent of bone loss. Nakagawa et al 9 , 10 reported that the recurrence rate was higher among rugby players compared with other athletes and that rugby players had a high recurrence rate despite a small glenoid defect. Therefore, the indications for stabilization surgery should be decided by considering both the extent of bipolar bone loss and the sporting category.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the type of sport also has a significant effect on recurrence, independent of bone loss. Nakagawa et al 9 , 10 reported that the recurrence rate was higher among rugby players compared with other athletes and that rugby players had a high recurrence rate despite a small glenoid defect. Therefore, the indications for stabilization surgery should be decided by considering both the extent of bipolar bone loss and the sporting category.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased redislocation rate in collision athletes with glenohumeral instability operated with the Bankart procedure. 1 , 2 , 3 Nonetheless, there is no universally accepted definition of “contact” sports in the literature. The most widely used classification is the one proposed by the American Academy of Pediatrics Committee on Sports Medicine.…”
mentioning
confidence: 99%
“…According to the review by Woolnough et al, 5 postage-stamp fractures were frequent in male patients, patients aged 25 years or younger, patients involved in sporting activities, patients who received initial stabilization with 3 or more anchors or conventional knot-tying anchors, and patients with osteolysis around the anchor sites. It is well known that young male patients and persons involved in sports have an increased risk of recurrent instability after arthroscopic repair, 13 and this review clearly showed that postagestamp fractures are not like the osteoporotic fractures frequently seen in elderly patients and instead appear to be characteristic of young active athletes. It has been reported that a small number of anchors is a risk factor for postoperative recurrence of instability, and use of at least 3 anchors during stabilization surgery is recommended.…”
Section: See Related Article On Page 2501mentioning
confidence: 77%